Pengaruh Motivasi dan Pelatihan Kerja Terhadap Peningkatan Kinerja Usaha Mikro, Kecil, dan Menengah Di Kecamatan Biringkanaya Kota Makassar - wuriyanti Saptorini; Andi Syahrum Makkuradde; Andi Hendra Syam (Jurnal Online Manajemen ELPEI, 2022)
The purpose of this study was to determine the effect of motivation and job training on micro, small and medium enterprises in Biringkanaya District, Makassar City This study uses a combined approach, namely using qualitative and quantitative approaches using primary data as a reference. The sample used in this study is the entire population, namely as many as 81 respondents This data collection technique uses a questionnaire consisting of several statements of the total number. The data analysis technique uses multiple linear regression techniques with simultaneous hypothesis testing (F test), partial test (t test) and coefficient of determination. The results of the study show that job training and motivation have a significant relationship with the performance of MSMEs in Biringkanaya District, Makassar City.